EKSPERIMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE TEAMS GAMES TOURNAMENT (TGT) DAN TIPE NUMBERED HEADS TOGETHER (NHT) PADA MATERI PERSAMAAN DAN PERTIDAKSAMAAN KUADRAT DITINJAU DARI KECEMASAN MATEMATIKA SISWA KELAS X SMA NEGERI SE-KABUPATEN PONOROGO - Haniah, Wahyu Nur; Budiyono, Budiyono; Usodo, Budi (Jurnal Pembelajaran Matematika, 2016)
Abstract: The purpose of this study was determine the effect of the learning models TGT, NHT, and direct learning model on mathematics learning achievement viewed from the students mathematics anxiety. This research was quasi experimental research with a 3x3 factorial design. The study population was all tenth grade students of Senior High Schools in Ponorogo district. The data analysis technique used was the two-way ANAVA with unbalanced cell. The results could be concluded as follows. 1) Students who were treated with the cooperative model of TGT and NHT have equal mathematics achievement, students who were treated with the cooperative model of TGT got better achievement than students treated by direct learning, in addition students who were treated with the cooperative models of NHT and direct learning have equal mathematics achievement, 2) Students with low and average mathematics anxiety got mathematics achievement better than students with high mathematics anxiety, then students with low mathematics anxiety got mathematics achievement better than students with average mathematics anxiety, 3) In each mathematics anxiety category, students who were treated with the cooperative model of TGT and NHT have equal mathematics achievement, students who were treated with the cooperative model of TGT got better achievement than students treated by direct learning, in addition students who were treated with the cooperative model of NHT and direct learning have equal mathematics achievement, 4) In each learning models, students with low and average mathematics anxiety got mathematics achievement better than students with high mathematics anxiety, then students with low mathematics anxiety got mathematics achievement better than students with average mathematics anxiety.Key words: Team Games TournamentÂ  (TGT), Numbered Head Together (NHT), Direct Learning, Mathematics Anxiety.